The Covid 19 And The Likes Of Possible Pandemic: An Islamic Way To Earnest Prophylaxis - Muhammad Dare Garba; Yusuf Olawale Owa-Onire Uthman (al-Afkar, Journal For Islamic Studies, 2023)
This study dealt with breaking out pandemics, which is not a new phenomenon. It could be traced back centuries ago in the history of the world. Islam prescribes different measures to contain it. More so, within the history of humans, there is Hong Kong/68 (H3N2) pandemic, and when the Russian contagious disease strain (HINI) resurfaced in 197, the contagious disease family originated from mammals and several other animals. This paper, therefore, examines the Covid 19 pandemic and its predictable like influenza in the future, showcasing the Islamic-social measures to deal with such viruses with references to its events in history. Descriptive and doctrinal methods are adopted to explain the Islamic and some social strategies in dealing with pandemics. Finally, the study recommended that the provision provided in the Islamic objective before the secular policy and development programs should be correctly implemented to save lives, taking good care of their health by eating a balanced diet and maintaining good health habits of their body and places of worship, even before disease challenges. While Muslims are also urged to understand their religion and every human should be a law-abiding citizen to tackle the menace of pandemics around the world.